Blending of a 3D cloud-like morphology with a 1D structure in a VO2/MXene nanocomposite to enhance the charge storage capability - Kumar N.; Ansari M.N.M.; Upadhyay S.; Gajraj V.; Chetana S.; Joshi N.C.; Sikiru S.; Sen A. (Royal Society of Chemistry, 2024)
Over the years, functional materials have been subject to intense research due mainly to their potential utilities in advancing the realm of nanotechnology. Here, a unique method is emphasized, probably for the first time, in breaking up MXene morphologies into tiny pieces using finer VO2 nanowires as templates. Scanning microscopy and X-ray spectroscopy techniques are used to describe this newly developed distinctive morphology. The morphological tension formed between the VO2 and the MXene surface significantly enhances the supercapacitive properties of VO2 at 286.0 F g?1, 2 A g?1 in a symmetric electrode configuration. The VO2 nanowire capacity increases by almost double on blending with MXene. An appreciable amount of energy is stored at 128 W h kg?1 and 1800 W kg?1. Better stability is also encountered with 97% capacity retention after the 10 000th cycle of galvanostic charge-discharge metrics. The three-dimensional cloud-like morphology of MXene surrounding VO2 nanowires helps in synergistically advancing their surface activity and safeguarding them against any pulverization. A promising good capacitive behavior can thus be built out of vanadium-based materials. 2023 The Royal Society of Chemistry.